Intelligent decision-support system to plan, manage and optimize water quality monitoring programs: design of a conceptual framework. Issue 4 (21st March 2021) - Behmel, S.; Damour, M.; Ludwig, R.; Rodriguez, M. J.
Abstract : This paper presents the conceptual framework of a holistic, intelligent decision-support system (IDSS) to plan, manage and optimize water quality monitoring programs (WQMPs) for surface waters. WQMPs are a crucial component of water management because information on water quality is essential when taking action such as legislative compliance, environmental projects, urban and infrastructure development. Planning, managing and optimizing WQMPs is a complex process and requires multiple variables, rules and subject matter expert knowledge. The specific goals of this paper were to (1) assess to what extent the subject domain (WQMPs) is deemed appropriate for an IDSS; (2) describe the design process of the conceptual framework; (3) present the main elements of the system architecture; (4) present two case studies that served as potential end users; (5) illustrate the applicability of the IDSS and (6) describe subsequent steps to further test the IDSS. The IDSS was developed on the premise that the proposed system could (1) improve quality, (2) capture undocumented expertise that is perishable or in short supply (tacit knowledge), (3) provide accessible expertise to novice users, (4) have a training effect on users, and (5) show that the system, even partially complete, could still be useful. Our initial assumptions regarding these points were validated through interviews with subject matter experts. The conceptual framework was designed based on a literature review, interviews with 44 subject matter experts from Europe, Canada and the United States, interaction with end users from two case studies in the Province of Quebec, Canada, and five information technology experts from Canada and Germany. The IDSS presented in this paper will facilitate the planning, management and optimization of WQMPs. It will be exportable to various watersheds and consider the WQMP planner's need to update the network rapidly if changes occur in human, financial and technical resources. HIGHLIGHTS: Holistic and adaptable decision-support system to plan, manage and optimize surface water quality monitoring programs Management and decision support system for knowledge acquisition processes on water quality System integrates tacit and explicit knowledge on water quality monitoring challenges Management and decision support system based on tacit knowledge from 44 experts and two case studies Adapted design methodology for an Intelligent decision-support system